Factors effecting drug relapse in Malaysia: an empirical evidence - Ibrahim, Fauziah; Kumar, Naresh (Canadian Center of Science and Education, 2009)
It has been noted that many drug addicts relapse to drug use after discharged from successful treatment and rehabilitation programs. Thus it is imperative and timely to address the issues that prompt relapsed addiction. 400 drug addicts on relapse cases were selected from eight drug rehabilitation centres throughout Peninsular Malaysia to examine factors influences the relapsed addiction to drug use. Consistent with previous research, self-efficacy, family support, community support and employers support were identified as main factors that influenced the relapsed addictions tendency amongst addicts. Suggestions to curb relapsed addiction to drugs were discussed in relation to the findings.